A Digital Multigate Doppler Method for High Frequency Ultrasound - Qiu, Weibao (MDPI, 2014)
Noninvasive visualization of blood flow with high frequency Doppler ultrasound has been extensively used to assess the morphology and hemodynamics of the microcirculation. A completely digital implementation of multigate pulsed-wave (PW) Doppler method was proposed in this paper for high frequency ultrasound applications. Analog mixer was eliminated by a digital demodulator and the same data acquisition path was shared with traditional B-mode imaging which made the design compact and flexible. Hilbert transform based quadrature demodulation scheme was employed to achieve the multigate Doppler acquisition. A programmable high frequency ultrasound platform was also proposed to facilitate the multigate flow visualization. Experimental results showed good performance of the proposed method. Parabolic velocity gradient inside the vessel and velocity profile with different time slots were acquired to demonstrate the functionality of the multigate Doppler. Slow wall motion was also recorded by the proposed method.